2012
DOI: 10.1007/s13361-012-0337-7
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Organic Ions at Ambient Surfaces in a Solvent-Free Environment

Abstract: Solvent-free ion/surface chemistry is studied at atmospheric pressure, specifically pyrylium cations, are reacted at ambient surfaces with organic amines to generate pyridinium ions. The dry reagent ions were generated by electrospraying a solution of the organic salt and passing the resulting electrosprayed droplets pneumatically through a heated metal drying tube. The dry ions were then passed through an electric field in air to separate the cations from anions and direct the cations onto a gold substrate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 48 publications
(52 reference statements)
0
22
0
2
Order By: Relevance
“…Similar rate enhancement was observed when one of the reactants present in the vapour phase was captured in microdroplets containing the second reactant [82]. Furthermore, Badu-Tawiah et al demonstrated efficient reaction between bare organic cations and ambient surfaces [83]. In that study, fully desolvated ambient 2,4,6-triphenylpyrylium cations produced using ESI were allowed to react with a dry film of ethanolamine on a solid surface.…”
Section: Ambient Surface Ionisation Techniquesmentioning
confidence: 60%
See 1 more Smart Citation
“…Similar rate enhancement was observed when one of the reactants present in the vapour phase was captured in microdroplets containing the second reactant [82]. Furthermore, Badu-Tawiah et al demonstrated efficient reaction between bare organic cations and ambient surfaces [83]. In that study, fully desolvated ambient 2,4,6-triphenylpyrylium cations produced using ESI were allowed to react with a dry film of ethanolamine on a solid surface.…”
Section: Ambient Surface Ionisation Techniquesmentioning
confidence: 60%
“…Cooks and co-workers also used reactive DESI to study reactions of organic molecules trapped in charged microdroplets and isolated solvent-free organic cations with molecules on surfaces [81][82][83]. Girod et al [81] demonstrated rate enhancements by several orders of magnitude for model bimolecular reactions occurring in microdroplets compared to bulk solution.…”
Section: Ambient Surface Ionisation Techniquesmentioning
confidence: 99%
“…Solvent evaporation leading to rate enhancement of chemical reactions has recently been reported for charged microdroplets reactor systems generated in reactive desorption electrospray ionization (DESI) [1,10,11] and ambient ion soft landing [12][13][14] experiments. Traditionally, the advantages of microreactor systems are recognized to include rapid mixing of reagents, effective control of reaction time, and the ability to control interfacial chemistry [15].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this type of electrospray (ESI [29,42,43]) is that it allows some solvent evaporation from the droplets during their transfer to the designated location, and the use of the derived charged microdroplets for surface reactions at atmospheric pressure. To effect surface reaction, the charged microdroplets containing the desired reagent ion were directed onto the reaction surface containing a nominally dry reagent using the ambient soft landing apparatus [39,44]. Under particular experimental conditions (discussed later), this apparatus allows focusing of the ions onto a 2 mm (diameter) spot size, producing no observable macroscopic solvent on the surface.…”
Section: Introductionmentioning
confidence: 99%